2021
DOI: 10.3390/rs13050879
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks for Road Sign Detection and Embedded Modeling Using Oblique Aerial Images

Abstract: Oblique photogrammetry-based three-dimensional (3D) urban models are widely used for smart cities. In 3D urban models, road signs are small but provide valuable information for navigation. However, due to the problems of sliced shape features, blurred texture and high incline angles, road signs cannot be fully reconstructed in oblique photogrammetry, even with state-of-the-art algorithms. The poor reconstruction of road signs commonly leads to less informative guidance and unsatisfactory visual appearance. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The potential that oblique photogrammetry brings is quite significant. Firstly, it provides a data source with distinct advantages: multiple views from different perspectives and significantly different image scales [19]. In addition, oblique photogrammetry carries the possibility of obtaining information about the location of an object in a terrain system and the use of the multitemporal feature [20].…”
Section: Related Workmentioning
confidence: 99%
“…The potential that oblique photogrammetry brings is quite significant. Firstly, it provides a data source with distinct advantages: multiple views from different perspectives and significantly different image scales [19]. In addition, oblique photogrammetry carries the possibility of obtaining information about the location of an object in a terrain system and the use of the multitemporal feature [20].…”
Section: Related Workmentioning
confidence: 99%
“…In the early stage of development, traditional machine learning methods have been used for scene classification tasks, such as support vector machine and bag of words [2,3]. Recently, deep learning methods have been proven to be effective for extracting image features [4][5][6][7][8], and many studies have demonstrated effective scene classification performance with the help of deep learning from various novel perspectives including self-supervised learning [9], data augmentation [10], feature fusion [11][12][13][14][15], reconstructing networks [16][17][18][19][20][21][22][23], integration of spectral and spatial information [24], balancing global and local features, refining feature maps through encoding method [25], adding a new mechanism [26,27], as well as introducing a new network [28], open set problem [29], and noisy label distillation [30]. However, a lack of annotated data has restricted the development of deep learning methods in scene classification due to the high cost of annotating data.…”
Section: Introductionmentioning
confidence: 99%